2018
DOI: 10.18632/oncotarget.25713
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole stimulates CD14+ myeloid cells to enhance T-cell activation and tumour cell killing

Abstract: Mebendazole (MBZ) was recently shown to induce a tumor suppressive M1 phenotype in THP-1 monocytes and macrophages. In the present study the immune effects of MBZ was further investigated using human peripheral blood mononuclear cells (PBMCs) co-cultured with tumour cells. The Biomap platform was used to screen for biomarkers induced from MBZ exposed co-cultures of T-cell receptor activated PBMCs, HT29 colon cancer cells and either human fibroblasts or human umbilical vein endothelial cells (HUVEC) cells. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Mebendazole had little or no effect on clustering and cytokine release in non-activated PBMCs, but increased clustering and released proinflammatory cytokines, including TNF-α, IL-1β, IFN-γ, and IL-6 in CD3/IL2-activated PBMCs, potentiating both tumor cell reduction and apoptosis ( 91 ). Mebendazole induced a proinflammatory (M1) phenotype of monocytic cells (THP-1) via ERK1/2 and TLR8-dependent inflammasome activation ( 48 ).…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…Mebendazole had little or no effect on clustering and cytokine release in non-activated PBMCs, but increased clustering and released proinflammatory cytokines, including TNF-α, IL-1β, IFN-γ, and IL-6 in CD3/IL2-activated PBMCs, potentiating both tumor cell reduction and apoptosis ( 91 ). Mebendazole induced a proinflammatory (M1) phenotype of monocytic cells (THP-1) via ERK1/2 and TLR8-dependent inflammasome activation ( 48 ).…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…We speculate that MBZ may counteract these immune suppressive effects by restoring ERK activity. We have also previously shown that MBZ induces an M1 phenotype in human macrophage models and potentiates the anti-cancer activity of CD3/IL-2 activated peripheral blood mononuclear cells (PBMCs), the effect being attenuated by removal of CD14+ myeloid cells 38 .…”
Section: Discussionmentioning
confidence: 95%
“…Its anti-cancer properties were notably demonstrated in gliomas [11,14,27] and there is currently 3 ongoing clinical trials in high-grade gliomas in both adult and pediatric patients (NCT01729260, NCT02644291 and NCT01837862). Furthermore, a recent phase I trial demonstrated that administration of MBZ concomitantly with radiotherapy and temozolomide chemotherapy was safe in high-grade glioma patients [28] Although multiple studies have highlighted different mechanisms of action of MBZ in cancer cells [12][13][14][15][16], including its effects on the microtubule network [8,11,14,17,18], its precise molecular target(s) in tumor cells remained to be ascertained. Herein, we used in silico target prediction to unveil novel therapeutic targets for MBZ in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of action have been proposed to explain the anticancer properties of MBZ. These include tumor angiogenesis inhibition [12,13], targeting of critical pathways involved in cancer such as Hedgehog signaling [14] and stimulation of anticancer immune response [15,16]. Most of these effects have been linked to the ability of MBZ to induce microtubule depolymerization in cancer cells [8,11,17,18].…”
Section: Introductionmentioning
confidence: 99%